Anti‐inflammatory disease‐modifying treatment and disability progression in primary progressive multiple sclerosis: a cohort study. (2nd November 2018) - Lorscheider, J.; Kuhle, J.; Izquierdo, G.; Lugaresi, A.; Havrdova, E.; Horakova, D.; Hupperts, R.; Duquette, P.; Girard, M.; Prat, A.; Grand'Maison, F.; Grammond, P.; et al.
Abstract : Background and purpose: Treatment options in primary progressive multiple sclerosis (PPMS) are scarce and, with the exception of ocrelizumab, anti‐inflammatory agents have failed to show efficacy in ameliorating disability progression. The aim of this study was to investigate a potential effect of anti‐inflammatory disease‐modifying treatment on disability outcomes in PPMS. Methods: Using MSBase, a large, international, observational database, we identified patients with PPMS who were either never treated or treated with a disease‐modifying agent. Propensity score matching was used to select subpopulations with similar baseline characteristics. Expanded Disability Status Scale (EDSS) outcomes were compared with an intention‐to‐treat and an as‐treated approach in paired, pairwise‐censored analyses. Results: Of the 1284 included patients, 533 were matched (treated, n = 195; untreated n = 338). Median on‐study pairwise‐censored follow‐up was 3.4 years (quartiles 1.2–5.5). No difference in the hazard of experiencing 3‐month confirmed EDSS progression events was observed between the groups [hazard ratio (HR), 1.0; 95% confidence interval (CI), 0.6–1.7, P = 0.87]. We did not find significant differences in the hazards of confirmed EDSS improvement (HR, 1.0; 95% CI, 0.6–1.6, P = 0.91) or reaching a confirmed EDSS step ≥7 (HR, 1.1; 95% CI, 0.7–1.6, P = 0.69). Conclusion: Our pooled analysis of disease‐modifying agents suggests that these therapies have no substantial effect on short‐ to medium‐term disability outcomes in PPMS.